Analisis Potensi Investasi Kabupaten Halmahera Barat - Jufri Jacob; Nonce Hasan (Kodepena Indonesia, 2024)
The research objectives are to provide an overview of investment potential based on the sectoral classification of West Halmahera Regency and to calculate the business/economic feasibility of several leading sector products in West Halmahera Regency. The type of research data uses quantitative and qualitative data consisting of primary and secondary data. The data analysis technique uses economic feasibility on commodities from potential sectors to be developed so that the analysis used in this research is Net Present Value (NPV), Internal Rate of Return (IRR), Return on Investment (ROI) and Payback Period (PP). The results showed that based on the analysis of investment potential in West Halmahera Regency, there are great opportunities in three main sectors, namely agriculture, fisheries and tourism. In the agricultural sector, leading commodities such as coconut, nutmeg, cocoa and cloves have significant room for development, especially with the availability of land that has not been fully utilised. The fisheries sector also has great potential with the abundance of marine and inland fisheries resources, although they have not been optimally utilised. In addition, the tourism sector, especially nature and marine tourism, shows promising prospects for further development, especially in the form of ecotourism and cultural tourism that can support regional development. In terms of business feasibility, economic analysis shows that superior products such as coconut, cocoa, and cloves have promising investment values based on economic indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). Overall, products from the agriculture and fisheries sectors in the region are worth investing in, with competitive profit opportunities. Therefore, it can be concluded that West Halmahera Regency has high investment potential in various sectors, with economic viability that supports long-term investment growth. Keywords: Investment Potential, Economic Feasibility, West Halmahera, NPV, IRR, ROI, PP, Agriculture, Fisheries, Tourism.